Nickel sulfide microsphere film on Ni foam as an efficient bifunctional electrocatalyst for overall water splitting. Issue 7 (10th December 2015) - Zhu, Wenxin; Yue, Xiaoyue; Zhang, Wentao; Yu, Shaoxuan; Zhang, Yuhuan; Wang, Jing; Wang, Jianlong
Abstract : A NiS microsphere film was grown in situ on Ni foam (NiS/Ni foam) via a sulfurization reaction as an efficient bifunctional electrocatalyst, with superior activity and durability for both the HER and OER in basic media. Abstract : Developing low-cost, efficient, and bifunctional electrocatalysts for both the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) is an appealing yet challenging task. Herein, for the first time, a NiS microsphere film was grown in situ on Ni foam (NiS/Ni foam) via a sulfurization reaction as an efficient bifunctional electrocatalyst for overall water splitting with superior activity and good durability. This NiS/Ni foam electrode delivers 20 mA cm −2 at an overpotential of 158 mV for the HER and 50 mA cm −2 at an overpotential of 335 mV for the OER in 1.0 M KOH. This bifunctional electrode also enables a high-efficiency alkaline water electrolyzer with 10 mA cm −2 at a cell voltage of only 1.64 V, which could be promising in water splitting devices for large-scale hydrogen production.